Pengaruh Model Pembelajaran Kooperatif Tipe TGT berbantuan Quizizz Terhadap Kemampuan Literasi Matematis Siswa - Hadi, Usman; Hayati, Laila; Novitasari, Dwi; Sripatmi, Sripatmi (Griya Journal of Mathematics Education and Application, 2025)
This study aims to determine the effect of the cooperative learning model, specifically the Teams Games Tournaments (TGT) type assisted by Quizizz, on the mathematical literacy skills of 11th-grade students at MAN 1 Mataram in the academic year 2024/2025. This research is a quasi-experimental study using a posttest-only control group design. The population consisted of three 11th-grade science classes with a total of 118 students, and the sample included two classes: XI IPA 1 as the control group, which received direct instruction, and XI IPA 2 as the experimental group, which received the TGT model assisted by Quizizz. The sampling technique used was cluster random sampling. Data were collected through a mathematical literacy skills test administered after the intervention and were analyzed using normality and homogeneity tests. Based on the results, a non-parametric test chi-square test was employed along with the calculation of the effect size. The findings showed a difference in the average scores between the control group (49) and the experimental group (78), indicating the influence of the TGT model assisted by Quizizz on students' mathematical literacy. The effect size value of d = 0.465 falls within the medium category, suggesting a moderate impact. Therefore, the TGT cooperative learning model assisted by Quizizz contributes positively to enhancing students' mathematical literacy, particularly in function-related topics such as trigonometry, logarithms, and algebra. Future studies are recommended to further explore the implementation of this model across different educational levels, subject matter, and broader learning contexts.